Economics of animal health and production [ - Rushton, Jonathan; Ellis, Peter R. (CABI, 2009)
The efficient functioning of the livestock sector, encompassing all facets of input supply, production, processing and marketing, is critical for food security and safety. This book covers the history of livestock and animal health economics, and theoryand tools for the economics of animal health and production.